Devising a method for strategic-oriented evaluation of the activities of logistics personnel taking into account the effect of risk and uncertainty factors - Vorkut, Tatiana; Volynets, Lyudmila (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of strategically-oriented assessment of the activities of an employee at an entity involved in the rendering of logistics services to internal and/or external clients (consumers) of the organization, taking into account the effects of risk and uncertainty factors. The task addressed is to improve the efficiency of decisions (according to a specified optimization criterion) in the field of logistics personnel management in the organization based on the further development of methodological approaches to assessing the activities of logistics personnel. A structural model of an integral indicator for strategically-oriented assessment of the activities of an employee of the organization involved in the provision of logistics services has been built. The hierarchical structural model involves establishing a connection between the system for assessing the activities of logistics personnel with the strategic goals of the organization. The study also reports a constructed mathematical model of an integral indicator for strategically-oriented assessment of the activities of an employee of the organization involved in the provision of logistics services, taking into account the effects of risk and uncertainty factors. A procedure for the interaction of these models has been proposed, owing to which a method of strategically oriented assessment of the activities of logistics personnel was suggested, taking into account the action of risk and uncertainty factors. Applying the method could make it possible to form integral and complex indicators for assessing the activities of logistics personnel, aimed at achieving the strategic goals of the organization. This would also enable determining general directions and building individual trajectories for the training and development of logistics personnel. The specified method is advisable to use when developing software for planning the logistics activities of enterprises